Application of zero phase wavelet on synthetic seismic signals with noise - Srinivas Goli, Sai; Papanaboyina, Sireesha; Ramesh Kanchumarthi, Satya; Rao Sanagapallea, Koteswara (International Journal of Engineering and Technology, 2018)
Detection of time of occurrences of different phases and frequencies is of highest importance in seismic reflected signals. Seismic reflection analysis gives us accurate information about the event detection, source acquisition of triggered seismic data and its mechanisms. In the present work an attempt is made to generate a synthetic seismic with noise generally present in the seismograph using. The synthetic seismic signal is extracted by zero phase wavelet. Crews software is used in this extraction. The zero phase wavelet could efficiently extract the seismic signal present in the reflected wave.Â Â